Planejando o desenvolvimento local sustentável : proposta de um sistema integrado de gestão ambiental urbano SIGAU no município de Laranjeiras/SE - Santos, Paulo Sérgio Melo dos (2010)
The environmental crisis established nowadays is a consequence of widespread natural degradation that has been going on during the last few decades. This crisis has several consequences for the contemporary societies, in different levels of influence: social, cultural and economic. The complexity of the network of causal relations involving the environmental crisis reaches, among others things, the urban centers. The municipality of Laranjeiras, State of Sergipe, has received a significant industrial boost at the beginning of the 1980s as a consequence of several developmental policies during the dictatorial period. Laranjeiras economic growth was mainly due to the mining industries located in the area. Although it possesses one of the highest per capita incomes in the state (achieved through industrial tax collection and royalties), Laranjeiras has a poverty incidence of 61%, and a great number of basic structural problems, such as lack of a sewer system and high unemployment and criminality rates. This contradictory scenario is clearly related to inefficient local public policies that are unable to manage the environmental and social problems caused by the mining industries. Considering this, the present study aims to develop an Integrated System of Urban Environmental Gestation (SIGAU), which has as central goal of improving the decision making process among the technical team and policy managers of Laranjeiras, mainly regarding the environmental issue. In specific terms, this means: selecting sustainable indicators that would help in the municipal management and planning related to a sustainable development; consider social, physical-space, environmental, economic and institutional dimensions in the urban management and planning in an integrated way; and finally, apply methods as a way to reach the ´´sustainability point´´ of different municipal indicators. In general terms it means this work is based on applied, exploratory and analytical procedures. The study is built on two analytical bases: a qualitative-intuitive one, and a more quantitativesystemic one. The data was collected by carrying out a survey in pre-existing databases, such as: Brazilian Institute of Geography and Statistics (IBGE), Laranjeiras´ City Hall (PML), CONDEM, ADEMA, IPHAN. The SIGAU uses the Participative Planning of the State, as well as the municipal Participatory Master, to favor the selection of sustainable indicators. An integrated evaluation was performed through the Decision Making Aid based on Multi-criteria Methods (MCDA). To measure the extent of Laranjeiras´ sustainability, the UNESCO method was applied. Lastly, to assist the selection of municipal projects the MACBETH tool was used, wich was based on GESPÚBLICA data for your implementation. The results presented here show that Laranjeiras has an unacceptable balance showing an urgent need for effective public policies directed to sort a local sustainable evelopment. Meanwhile, the proposed SIGAU cannot give up of the system´s gear key-point: the popular involvement. Decentralization should also be encouraged and cultivated in public administration, making the whole process more transparent and attractive for all social actors. The community must discover the SIGAU, they should participate, acting in a representative way through civil society. This is the only way the SIGAU could work more efficiently and achieve the optimal balance.